2018
DOI: 10.1111/jon.12550
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Cerebellar Hemisphere Tumors: Combining Apparent Diffusion Coefficient Histogram Analysis and Structural MRI Features

Abstract: In pretreatment differentiation of cerebellar tumors, the ADC histogram analysis is particularly helpful for distinction of medulloblastomas from other subtypes, and differentiation of the two most common adult tumors (ie, metastases and hemangioblastomas) from each other. Combination of structural imaging features and ADC histogram analysis can help with pretreatment differentiation of cerebellar tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…A major goal of the present study was to assess potential associations between the genetic subtypes and immunohistochemical parameters of medulloblastoma using quantitative (ADC) MRI, as comparable literature data are sparse. Considering the whole study population ( n = 32), the calculated ADC mean within the solid tumor components was 586 (10 −6 mm 2 /s), which is in the range of data reported by other authors who did not explicitly investigate genetic subtypes 13,20,22 . Similar to the results of Perreault and colleagues, 12 difference of the ADC mean between genetic subtypes did not reach statistical significance, which was possibly caused by the low sample size of the WNT‐activated subgroup ( P = .080).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A major goal of the present study was to assess potential associations between the genetic subtypes and immunohistochemical parameters of medulloblastoma using quantitative (ADC) MRI, as comparable literature data are sparse. Considering the whole study population ( n = 32), the calculated ADC mean within the solid tumor components was 586 (10 −6 mm 2 /s), which is in the range of data reported by other authors who did not explicitly investigate genetic subtypes 13,20,22 . Similar to the results of Perreault and colleagues, 12 difference of the ADC mean between genetic subtypes did not reach statistical significance, which was possibly caused by the low sample size of the WNT‐activated subgroup ( P = .080).…”
Section: Discussionsupporting
confidence: 73%
“…Considering the whole study population (n = 32), the calculated ADC mean within the solid tumor components was 586 (10 −6 mm 2 /s), which is in the range of data reported by other authors who did not explicitly investigate genetic subtypes. 13,20,22 Similar to the results of Perreault and colleagues, 12 difference of the ADC mean between genetic subtypes did not reach statistical significance, which was possibly caused by the low sample size of the WNT-activated subgroup (P = .080). However, the mean ADC value was lowest in this subgroup (480 [10 −6 mm 2 /s]); this finding is comparable to recently published data of Reddy and colleagues.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Several studies have investigated the values of DWI and ADC in the differential diagnosis of hemangioblastoma and other common tumors in the posterior fossa, yet optic nerve tumors have not been focused on. Most studies concluded that the ADC values of hemangioblastoma were significantly higher than those of metastatic tumors (39)(40)(41)(42). Hemangioblastoma is also found to have higher ADC values than most primary tumors including meningioma and medulloblastoma, except pilocytic astrocytoma (PA) according to Payabvash and colleagues (40).…”
Section: The Mri Findings Of Optic Nerve Hemangioblastomamentioning
confidence: 99%
“…However, the radiological diagnostic accuracy largely depends on the judgment and expertise of radiologists. Besides, brain metastatic tumor may present various MR image features based on their primary origins, and the various appearances of medulloblastoma and hemangioblastoma could potentially lead to misleading conclusions in some cases (Poretti et al, 2012; Millard and De Braganca, 2016; Payabvash et al, 2018). However, it is important to make preoperative diagnosis accurately and early as the treatment strategies and prognoses of patients are dramatically different (Grossman and Ram, 2016; Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%